2012
DOI: 10.1002/jor.22177
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification counteracts adverse effects associated with immobilization after flexor tendon repair

Abstract: SUMMARY Although post-rehabilitation is routinely performed following flexor tendon repair, in some clinical scenarios post-rehabilitation must be delayed. We investigated modification of the tendon surface using carbodiimide derivatized hyaluronic acid and lubricin (cd-HA-Lub) to maintain gliding function following flexor tendon repair with postoperative immobilization in a in vivo canine model. Flexor digitorum profundus tendons from the 2nd and 5th digits of one forepaw of six dogs were transected and repai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Second, we did not test either the cell-based therapy or surface modification alone. However, some studies have shown that bone marrow stromal cells do increase tendon healing capacity [8,10,15], and others have shown that surface modification decreases tendon adhesions [14,40]. Therefore, the purposes of our study were to investigate the effects of combining these treatments on postoperative adhesion formation and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…Second, we did not test either the cell-based therapy or surface modification alone. However, some studies have shown that bone marrow stromal cells do increase tendon healing capacity [8,10,15], and others have shown that surface modification decreases tendon adhesions [14,40]. Therefore, the purposes of our study were to investigate the effects of combining these treatments on postoperative adhesion formation and tendon healing.…”
Section: Discussionmentioning
confidence: 99%
“…The toes were operated under sterile conditions and tourniquet control using elastic bandages. A zigzag incision was made in the plantar skin between the proximal interphalangeal (PIP) and distal interphalangeal (DIP) joints, which is equivalent to zone 2 in the human hand 60 61 . Through a 1.0-cm long longitudinal incision through the tendon sheath, a transverse cut of the FDP tendon was made with a sharp scalpel at the level about 1.0 cm distal to the PIP joint with the toe in extension.…”
Section: Methodsmentioning
confidence: 99%
“…Although the healing strength of the tendon itself was quite low compared to the force measured in in vivo tendon repair studies,[53, 54] this is the strength of the healing tissue alone without any suture to supplement the strength. The healing strength of MDSCs with GDF-5 group was about twice as high as the strength of the repaired tendons without added cells or with BMSCs alone at 2 and 4 weeks.…”
Section: Discussionmentioning
confidence: 99%